Anti-biofilm Activities from Resveratrol against Fusobacterium nucleatum - He, Zhiyan; Huang, Zhengwei; Zhou, Wei; Tang, Zisheng; Ma, Rui; Liang, Jingping (Frontiers in Microbiology, 2016)
Fusobacterium nucleatum is a Gram-negative, anaerobic bacterium that plays an important role in dental plaque biofilm formation. In this study, we evaluate the effect of resveratrol, a phytoalexin compound, on F. nucleatum biofilm formation. The effects of different concentrations of resveratrol on biofilms formed on 96-well microtiter plates at different time points were determined by the MTT assay. The structures and thicknesses of the biofilm were observed by confocal laser scanning microscopy (CLSM), and gene expression was investigated by real-time PCR. The results showed that resveratrol at sub-MIC levels can significantly decrease bioﬁlm formation, whereas it does not affect the bacterial growth rate. It was observed by CLSM images that the biofilm was visually decreased with increasing concentrations of resveratrol. Gene expression was down regulated in the biofilm in the presence of resveratrol. Our results revealed that resveratrol can effectively inhibit bioﬁlm formation.